SOCIAL MEDIA OPTIMIZATION OF RAMAMPA RESTO & BAR AS A VISUAL STRATEGY - Oei, Monique Pricilya; Christianna, Aniendya (International Review of Humanities Studies, 2025)
In the digital era, social media has become an important marketing tool for businesses, including the culinary industry. This study examines the use of motion graphics to develop the social media presence of Rarampa Resto and Bar, a restaurant serving Manado cuisine and healthy MSG-free food, located in South Jakarta. Although the restaurant has a loyal customer base, particularly from the 40-60 age group, its social media content fails to attract younger audiences, especially millennials, who seek unique and authentic culinary experiences. This study suggests that Rarampa's social media content, which mainly focuses on event photography and the restaurant's ambiance, is ineffective in capturing the attention of younger audiences. Therefore, the use of illustrations and motion graphics is proposed to create more dynamic and appealing visual content. By incorporating semi-cartoon illustration styles and motion graphic elements, Rarampa can build a stronger visual identity, engage younger audiences, and increase interaction on social media. The research employs a qualitative descriptive approach, using data collection methods such as observation, interviews, and documentation. The results of this study are expected to provide insights on how to optimize the use of motion graphics to attract younger audiences and enhance the visual appeal of Rarampa Resto and Bar's social media.